Patent foramen ovale in young stroke patients: diagnostic challenge and a new approach to the secondary prevention (a case report and review of literature) - Beržanskytė , I.; Valaikienė , J.; Jatužis , D. (Neurologijos seminarai, 2018)
Patent foramen ovale (PFO) occurs in about 25% of healthy adults, however, it is significantly more common among patients with cryptogenic stroke. Although PFO might be a direct cause of ischemia, it is often an accidental finding in stroke patients. In most cases, cryptogenic stroke with PFO is just a presumed diagnosis as it is difficult to prove PFO as etiological factor. Randomized trials and meta-analysis have showed controversial results in searching for the most effective prevention of cryptogenic stroke with PFO recurrence in the last six years. Nevertheless, currently available data suggests that PFO closure is superior to medical therapy. Two problems remain in clinical settings: identification of patients who would benefit from PFO closure most and the exact indications for intervention. In this article we present a clinical case and review literature examining diagnostic and secondary prevention of cryptogenic stroke with PFO.
Keywords: patent foramen ovale; cryptogenic stroke; embolic stroke of undetermined source; paradoxical embolization